Sensitive and specific markers for insulin resistance, hyperandrogenemia, and inappropriate gonadotrophin secretion in women with polycystic ovary syndrome: a case-control study from Bahrain - Al-Ayadhi MA; Golbahar J; Gumaa K; Das NM (Dove Medical Press, 2012)
Jamal Golbahar,1,2,* Maha Al-Ayadhi,2,* Negalla Mohan Das,2 Khalid Gumaa,2 1Department of Molecular Medicine, Al-Jawhara Centre for Genetic Diagnosis and Research, 2Department of Medical Biochemistry, College of Medicine and Medical Sciences, AGU, Manama, Bahrain *These authors contributed equally to this articleBackground: In women with polycystic ovary syndrome (PCOS), despite a high prevalence of insulin resistance, hyperandrogenemia, and disturbances in the secretion of gonadotrophin, the principal causes of biochemical abnormalities and the best endocrine markers for PCOS have not been fully identified.Subjects and methods: Serum levels of insulin, glucose, follicle-stimulating hormone (FSH), luteinizing hormone (LH), total testosterone, estrogen, sex hormone-binding capacity (SHBG), and other related indices such as homeostasis model assessment, insulin glucose ratios, LH/FSH ratios, and the free androgen index (FAI) were determined and compared in women with PCOS (n = 50) and women without PCOS (n = 50).Results: In multivariate logistic regression analyses, among all insulin resistance indices, only hyperinsulinemia (odds ratio [OR] = 2.6; confidence interval [CI]: 1.3–5.2; P = 0.008) was significantly and independently associated with PCOS when adjusted for body mass index (BMI), hyperandrogenemia, and LH/FSH ratios. The LH/FSH ratio (OR = 5.4; CI: 1.2–23.0, P = 0.03) was the only marker among those indices for inappropriate gonadotrophin secretion that significantly and independently associated with PCOS when adjusted for BMI and hyperinsulinemia. Among those indices for hyperandrogenemia, FAI (OR = 1.1; CI: 1.0–2.7; P = 0.02) and SHBG (OR = 1.2; CI: 1.2–3.4; P = 0.03) were significantly and independently associated with PCOS when adjusted for BMI and hyperinsulinemia. In addition, receiver operating characteristic analysis showed that the best predictive markers for PCOS were insulin (area under the curve [AUC] = 0.944; CI: 0.887–0.989), FAI (AUC = 0.932; CI: 0.895–0.993), SHBG (AUC = 0.924; CI: 0.87–0.978), and LH/FSH ratios (AUC = 0.906; CI: 0.821–0.965).Conclusion: For insulin and LH/FSH ratios, FAI, and SHBG seemed the best predictors and markers for insulin resistance, inappropriate gonadotrophin secretion, and hyperandrogenemia, respectively, with high sensitivity and specificity for identifying Bahraini women with and without PCOS.Keywords: polycystic ovary syndrome, insulin resistance, gonadotrophin, hyperandrogenemia, diagnostic markers